Antiphospholipid antibodies in the obstetric antiphospholipid syndrome: Detection and antibodies profile at the Maternity and Neonatal Medicine Center of Monastir, Tunisia. Issue 3 (18th January 2022) - Khefacha, Linda; Rassas, Rania; Bergaoui, Haifa; Mustapha, Henda; Faleh, Raja; Sakly, Nabil; Sassi, Mouna
Abstract: Purpose: This study aimed to implement lupus anticoagulant (LAC) detection techniques according to the International Society on Thrombosis and Hemostasis (ISTH) recommendations, in the Biological Laboratory of the Maternity and Neonatal Medicine Center (Monastir, Tunisia) and to evaluate the profile and the prevalence of antiphospholipid antibodies (aPL) in the obstetric antiphospholipid syndrome (OAPS). Methods: We collected two groups: a "case group" (53 women who presented one or more obstetrical criteria of APS) and a "control group." LAC was detected following the four steps recommended by ISTH 2009. Anticardiolipin (aCL) and antibeta‐2‐glycoprotein I (aβ2GPI) antibodies testing were performed by enzyme‐linked immunosorbent assay (ELISA). Results: aPL were found in five patients: three patients with isolated LAC, one patient with isolated IgG aCL, and one patient with triple positivity (LAC, aCL IgM, aβ2GPI IgM). Concerning LAC, 13 (24.52%) of 53 patients had a screening step with at least one positive test. The mixing step was positive in four patients and then confirmed in the confirmatory test. Thus, the prevalence of LAC in our study group is 7.54%. Surprisingly, among these positive patients, one patient had an associated combined factor V (FV) and factor VIII (FVIII) deficiency. Conclusion: There is no single test and no algorithm that can detect all types of LAC. It seems that the recent 2020 ISTH algorithm allows a better detection of low activity LAC than the 2009 algorithm. In our study, the most frequently identified antiphospholipid antibodies were LAC more than aCL and aβ2GPI.